2023
DOI: 10.1002/cncr.34787
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in patients with chronic lymphocytic leukemia treated with ibrutinib: Focus on hypertension and cardiovascular toxicity

Abstract: Background: Continuous ibrutinib administration is needed to maintain efficacy in patients with chronic lymphocytic leukemia (CLL) and, as such, long-term toxicity is a concern. The authors report the 5-year follow-up of patients with CLL who received treatment with ibrutinib with a focus on hypertension and cardiovascular toxicities.Methods: Patient characteristics were assessed, including blood pressure, cardiovascular disease, disease progression, and death. Univariate logistic regression analysis assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In previously published real‐world studies with varying follow‐up times, the majority shorter than ours, the incidence ranged between 3% and 17%. In these studies, AF was reported as cumulative incidence at the end of follow up, and therefore a direct comparison with our data is not always possible 6,18,20,21,24–26 . Also, real‐world data from long‐term follow‐up are limited.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previously published real‐world studies with varying follow‐up times, the majority shorter than ours, the incidence ranged between 3% and 17%. In these studies, AF was reported as cumulative incidence at the end of follow up, and therefore a direct comparison with our data is not always possible 6,18,20,21,24–26 . Also, real‐world data from long‐term follow‐up are limited.…”
Section: Discussionmentioning
confidence: 85%
“…In these studies, AF was reported as cumulative incidence at the end of follow up, and therefore a direct comparison with our data is not always possible. 6,18,20,21,[24][25][26] Also, real-world data from long-term follow-up are limited. However, in a prospective study in which patients were monitored with ECG at least every third month, the cumulative incidence was reported to be 38% at 2 years.…”
Section: Discussionmentioning
confidence: 99%